Denture disinfection by brushing and 6% hydrogen peroxide immersion on denture base resin after biofilm formation: An in vitro study - Manikya Shastri; Shalini Joshi; Chandrashekar Sajjan; Priyanka Konin (Wolters Kluwer Medknow Publications, 2018)
Background: Biofilm formation on acrylic dentures is often seen in denture wearers for which wide variety of denture cleansers are available. This study uses the commonly available 6% British Pharmacopoeia grade 20 volume hydrogen peroxide as denture cleanser. Aim: The aim of this study was to evaluate colonization and population dynamics of oral pathogenic microbial biofilm formation after assigning to one of the cleansing methods, manual brushing, or compound method (manual brushing with soft bristle wetted in distilled water and rinsed then immersion in 6% hydrogen peroxide solution) for the heat-cure acrylic denture base resin. Materials and Methods: Specimens of heat-cure acrylic resins discs were fabricated n = 120. Specimens n = 60 were placed in bacterial culture (Group I) and n = 60 were placed in fungal culture (Group II) until the formation of a biofilm which then was subjected to denture cleansing. They were then immersed in respective broth. The specimens were discarded, and Petri plate was incubated, and colony-forming units (CFUs) were counted. Values of microorganisms were grouped and analyzed according to the different hygiene methods by the Kruskal-Wallis test. Pairwise comparison was done by Mann-Whitney U-test. Results: The CFU in Group I and Group II after brushing was 60 CFU/ml and 50 CFU/ml, respectively. The CFU in Group I and Group II after subjecting to compound method was 1 CFU/ml. Conclusion: The compound method of this study was better when compared to only brushing method. Therefore, for the better maintenance of oral hygiene in denture wearers, the dentures need to be cleaned by manual brushing followed by immersion in hydrogen peroxide solution.